Judges, politics and the Irish constitution - Cahillane, Laura; Gallen, James; Hickey, Tom (Law teacher) (Manchester : Manchester University Press, 2017)
This volume brings together academics and judges to consider ideas and arguments flowing from the often complex relationships between law and politics, adjudication and policy-making and the judicial and political branches of government. Contributors explore numerous themes, including the nature and extent of judicial power, the European Court of Human Rights decision in O'Keeffe v Ireland, the process of appointing judges and judicial representation, judicial power and political processes.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 3, 2017).
Keywords: Ireland; Judicial power -- Ireland; Ireland -- Politics and government -- 21st century; Law; Laws of specific jurisdictions & specific areas of law